Rowing style indicator - Kleshnev, V. (Rowing Biomechanics Newsletter, 2015)
In this article an indicator of leg and trunk coordination during the beginning of the drive will be defined, which is related to rowing style. It is clearly shown that "catching through the stretcher" and "slide shooting" are two different things.The best drill to develop the correct segments coordination is rowing "catches only": after a quick "catch through the stretcher", the drive should be cut at the position on Fig.3,c - at knee angle 90deg and handles located on top of the stretcher. The trunk should firmly hold the load and its angle should not be changed.